School Management Factors Affecting Student Quality: A Case Study of the Thai Triam Udom Suksa Pattanakarn School Group - Supakrit Ditsuwan; Aukkapong Sukkamart (My University, 2022)
The research objectives were to study the factors of school management and their guidelines that affect learner quality. The sample was drawn from one of Thailand's 19 Triam Udom Suksa Pattanakarn (TRIAMPAT) group schools which have an enrollment of 30,644 students and 1,404 educators. Using a mixed research methodology and stratified random sampling 246 teachers and administrators were selected from 1,404 educators. This included 19 school administrators, 56 deputy administrators, 19 academic supervisors, and 152 teachers from eight learning groups. Descriptive statistics included the percentage, mean, and standard deviation used. Stepwise multiple regression and content analysis were also used. The results revealed that two factors affect institutional management and have a statistically significant effect on learner quality. These were the learning resource, media, technology, innovation, and research (x5) factors and the curriculum and teaching-learning system (x6) factors at the 0.01 level, with a predictive coefficient (R2 ) of 0.35. This indicates that x5 and x6 together predicted the quality of learners in the TRIAMPAT school group by 35%.
Keywords: Stratified Sampling; Affect; Sample (material); Educational Assessment and Improvement